O corpo da dança da fala: formas pedagógicas no maracatu - Nascimento, Gabriel Mesquita do [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This is a research in education on the oral tradition of African matrix in popular cultures, traditional groups and communities. Through the oral tradition happens the human constitution grounded in the ancestrality, resisting the domination processes of the Eurocentric modernity/coloniality and schooled mentality. In this way of educating, the ancestral identities are formed and can thrive, they are not loosened from memory along the historical resistance path since the ancestors and the colonialism. It is not possible to unlink past from present, education from life. It is an ethnographic research in traditional groups and communities of African matrix (Maracatu), theoretically based on the historical-cultural perspective, trying to understand the educative processes of human constitution. Proposes a dialog with the Paulo Freire's thinking and the decolonial thinking, given the research characteristics. Assuming, from the bibliography, that by the oral tradition of African matrix, in Brazil history and ancestry are perpetuated by the transmission of wisdom and knowledge through generations, and at the same time resisting the historical attempts of domination, the research answers to the following objective: investigate how the educative processes in the oral tradition of African matrix happens, and how this processes contribute to the human constitution of the communities' people. From the field research, the emerging reflections point to the transmission of wisdom and knowledge through the orality of African matrix as a educative process of human constitution that has the conscience and exercise of the ancestrality as its guideline. It also points to the conscience of the ancestrality as an educative element to freedom, as the traditional groups and communities of African matrix keep reaffirming to the world its ways of resisting and re-existing.

O trabalho aborda a educação pelas tradições orais de matriz africana nas culturas populares, povos e comunidades tradicionais. Por meio da oralidade é possibilitada a constituição humana fundada na ancestralidade, resistindo à pressão dos processos de dominação da modernidade/colonialidade e da mentalidade escolarizada, de base eurocêntrica. Nesta maneira de educar, se formam e permanecem as identidades ancestrais, não se perdem da memória o longo caminho de resistência ao colonialismo dos antepassados. Não desvincula-se o passado do presente, a educação da vida. Foi realizada pesquisa etnográfica em grupos e comunidades tradicionais de matriz africana (Maracatu), com base nas contribuições da perspectiva histórico-cultural, na busca pela compreensão dos processos educativos de constituição humana. Propõe ainda um diálogo com o pensamento freireano e com o pensamento decolonial. Partindo do pressuposto bibliográfico de que no Brasil, pela tradição oral de matriz africana, se perpetuam a história e a ancestralidade por meio de transmissões de saberes e conhecimentos entre gerações ao tempo em que resiste aos movimentos históricos de dominação, a pesquisa atende ao objetivo de: investigar como acontecem os processos educativos na tradição oral de matriz africana e de que maneira contribuem para a constituição humana das pessoas que compõem suas comunidades. Além disso, enuncia-se que o exercício da consciência ancestral se torna elemento educativo para a liberdade, na medida em que os grupos e comunidades tradicionais de matriz africana permanecem reafirmando perante o mundo suas formas de resistir e reexistir.
Keywords: Maracatu; Tradição oral; Cultura popular; Educação não-formal; Popular culture